Karakteristik Minyak Atsiri Dari Kulit Jeruk Manis, Kulit Jeruk Purut, Dan Kulit Jeruk Bali Dengan Metode Distilasi - Mukhtar, Muharnif; Ridho, Davidsyah; Suherman, Suherman; Khair, Hadriman (Rekayasa Material, Manufaktur dan Energi, 2026)
The distillation method is one way to produce essential oils from various parts of plants such as flowers, stems, bark and fruit, seeds and roots. This process has the advantage of oil purity and lower costs. The selection of sweet orange peel, kaffir lime peel and grapefruit peel as raw materials for making essential oils is due to their easy availability with fairly good essential oil characteristic quality. This study aims to obtain the best characteristic quality among the three types of peel used so that it is suitable for its use. The characteristics of essential oils analyzed include yield, acidity level (pH), water content, aroma resistance and color. The quality of essential oil characteristics greatly influences the use of essential oils in the industrial world such as food, beverages, perfumes, medicines and cosmetics. Based on the results obtained, kaffir lime peel produced the highest yield of 1.24%, the lowest water content of 9.21 indicating quality essential oil, the highest acidity level (pH) with a pH of 4.59 and a slightly yellowish clear color.